Community perspectives on barriers and challenges to HIV pre-exposure prophylaxis access by men who have sex with men and female sex workers access in Nigeria - G. Emmanuel; M. Folayan; G. Undelikwe; B. Ochonye; T. Jayeoba; A. Yusuf; B. Aiwonodagbon; C. Bilali; P. Umoh; K. Ojemeiri; A. Kalaiwo (BMC Public Health, 2023)
10p.